Insights into the preparation, properties, application in food of polysaccharide-based edible films and coatings: An updated overview - Hongkun Xue; Junyao Feng; Kaixuan Zhang; Yu Wang; Xiaojun Liao; Jiaqi Tan (Current Research in Food Science, 2025)
Polysaccharide-based edible films and coatings (PEFCs), as an innovative technology in the food industry, are increasingly receiving extensive attention due to their non-toxic, strong biodegradability, and excellent biocompatibility. Numerous studies have demonstrated that PEFCs could effectively regulate water migration and oxygen permeability, thereby prolonging the shelf life of food, mitigating spoilage, and minimizing nutrient loss. Hence, PEFCs are widely used in packaging for fruits, vegetables, fish, meat, and dairy products. In recent years, mounting studies have focused on the preparation methods of PEFCs and their applications in food. Currently, PEFCs are usually prepared by casting, extrusion, dipping, etc. In-depth study of the physicochemical properties (mechanical and barrier properties) and functional properties (antibacterial and antioxidant properties) of PEFCs has important guiding significance for designing of packaging materials with specific functions. Hence, this paper systematically reviews the raw materials and preparation methods of PEFCs. Moreover, the review systematically outlines the physicochemical and functional properties of PEFCs. Furthermore, the article systematically introduces the application of PEFCs in the food (fruits and vegetables, fish, meat, and dairy products) industry. Future research should focus on developing safe and environmentally friendly PEFCs, continuously optimizing the preparation process and performance, and expanding their application fields. The results indicate that bio-packaging materials made from polysaccharides provide great potential for enhancing food quality and safety, and reducing the environmental pollution.